2023
DOI: 10.1111/jvim.16745
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic and saphenous venous blood collected by continuous heating of the paws compared with arterial blood for measurement of blood gas values in well‐perfused dogs

Abstract: Background “Arterialization” of the dorsal hand vein is well‐established in human medicine, but not in veterinary medicine. Objectives To compare cephalic and saphenous venous blood collected by continuously heating the paws to 37°C (“arterialization”), with arterial blood (AB) for measurement of blood gas variables in well‐perfused dogs. Animals Eight healthy dogs. Methods Experimental study. Fore and hind paws were continuously heated to 37°C to “arterialize” cephalic and saphenous venous blood. AB and “arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…Furthermore, compared with the clinical limits predefined by the authors in this study (± 0.1), the LOAs being included inside those limits suggests the interchangeability of venous -whether jugular or saphenous -and arterial pH. Results from this work agree with most of the studies that have been conducted in human (Bloom et al, 2014;Byrne et al, 2014;Nanjayya et al, 2020) andveterinary (Pang et al, 2009;Kadwa et al, 2022;Shiroshita et al, 2023) medicine. Variations of pH between venous and arterial values are not of clinical impact in healthy, anesthetized, mechanically ventilated dogs.…”
Section: Phsupporting
confidence: 85%
See 4 more Smart Citations
“…Furthermore, compared with the clinical limits predefined by the authors in this study (± 0.1), the LOAs being included inside those limits suggests the interchangeability of venous -whether jugular or saphenous -and arterial pH. Results from this work agree with most of the studies that have been conducted in human (Bloom et al, 2014;Byrne et al, 2014;Nanjayya et al, 2020) andveterinary (Pang et al, 2009;Kadwa et al, 2022;Shiroshita et al, 2023) medicine. Variations of pH between venous and arterial values are not of clinical impact in healthy, anesthetized, mechanically ventilated dogs.…”
Section: Phsupporting
confidence: 85%
“…-1.90 mmHg to 10.26 mmHg). Results from this work reflect what has been reported in both human (Bloom et al, 2014;Byrne et al, 2014;Chung et al, 2019;Nanjayya et al, 2020) and veterinary (Tamura et al, 2015;Kadwa et al, 2022;Shiroshita et al, 2023) medicine, where the reported MD between venous and arterial pCO 2 ranges between 4.15 mmHg (Byrne et al, 2014) and 4.41 mmHg (Bloom et al, 2014) in humans, and between 2.00 mmHg (Kadwa et al, 2022) and 5.80 mmHg (Tamura et al, 2015) in dogs, values that are superimposable to the ones that we found in our population.…”
supporting
confidence: 89%
See 3 more Smart Citations